EARLY DOWNHOME BLUES IN AMERICAN CULTURE - Djuhertati Imam Muhni (Humaniora, 2000)
People's traditional music and the way people behave when performing it are symbolic expressions of broad cultural pattern and social organization . In other words music is a part of men's learned heritage . Hence this study is about music in a given culture, specifically blues in American culture . Allen Trachtenberg stated that blues songs are inheritance from the American past for negotiating black people's lives as Americans . In the experience of blues the African-Americans find themselves caught up in questions of self identity, authority, definition, and nationality . In its origin the blues has been black's music, but in its diffusion, the blues addresses and implicates both whites and blacks . For whites, the experience of the music is a relationship, a form of interaction : for whites to fill and claim the blues as part of their own inheritance means to recognize the blacks as Americans and to confront the continuing presence of race-definition inequalities in the common culture (Trachtenberg, 1994 : xi-viii) . The blues urges all Americans to feel the rhythm, the lyric, and the innuendo and to learn their common paradoxical condition : the interchangeability of race and culture within the national identity . Ought's a ought, figger's a figger ; All for the white and none for the niger (White, 1965 :383) . Blues indicates American conflict and struggle : the racial issues that are never far 212 from the beat of the downhome blues are transposed into a new space of contest and challenge (Trachtenberg, 1994 : xii) . Scope and Approach of Discussion There are two major types of early blues songs, namely downhome and vaudeville blues. Downhome blues is mostly sung by men, while Vaudeville by women singers . Originally downhome blues is folk music, but since 1920 with the recording industry it has become pop music . Vaudeville, on the other hand, is pop music right from the start . Most downhome singers sing accompanied by his own guitar-playing, whereas Vaudeville singers almost always sing in front of a jazz group . Vaudeville singers were mostly black women with backgrounds in musical shows ; they were professionals taking pride in their ability to deliver any kind of songs . Vaudeville blues was popular music, not folk music, their lyrics were usually composed by professionals black musicians. Most vaudeville blues songs from the 1920s resembled that of today's musical comedies . Influenced by genteel white taste, vaudeville singers strove for dramatic delivery, enunciating the words of the lyrics in standard English pronunciation (Titon, 1994 : xvii) . Not minimizing the importance of vaudeville blues, this study will only concern with downhome blues, leaving the former for further study .